Simulation Study of High Performance Thin Film Solar Cell Based of Perovskite n- CdS/p- CH3NH3SnI3 - Raed Maher Humaidan; Falah Mohammed Abed; Ghaith Thaaer Fadhil Al-Doori (Universitas Muhammadiyah Sidoarjo, 2026)
Solar cells fabricated of perovskite metal halide have experienced major improvement in the last few years. There is research interest in lead-free perovskite solar cells (PSCs) because lead in lead halide perovskites is believed to be toxic. CH3NH3SnI3 seems to lose ba a good alternative to CH3NH3PbX3. The impact of different parameters on the performance of the perovskite solar cells was learned by us in this paper through the software PC1D simulation. The cell configuration is made of three layers of n- CdS/p- CH3NH3SnI3/p- InP. In this study, I explore the effect of varying CH3NH3SnI3 absorber layer thickness and doping concentration 0.5 to 5 µm and 1015 to 10 -3 without a back surface field (BSF) layer. The n-CdS/p- CH3NH3SnI3 heterojunction was enhanced with a BSF layer to enhance solar cell performance. The effect of the thickness and doping concentration of the Back Surface Field layer (of 0.5 _ 5 )µm and 1015 -1020 cm-3 respectively were explored. The optimal doping concentration and thickness of the p- CH3NH3SnI3 and p-InP layers yielded the highest efficiency η = 24. 78 A/cm2 Jsc 34mA/cm2, Voc=0.81 and FF=90 A. The cell operating temperature was also experimented and the range was deposited between 300k to 400k and the findings revealed that the optimum was at 300k.